Post a New Question

algebra

posted by on .

Hey, I don't undertand how to solve this equation using substitution.

3y = -1/2x + 2
y= x + 9

  • algebra - ,

    sub the 2nd into the 1st

    3y = (1/2)x + 2
    3(x+9) = (-1/2)x + 2
    3x + 27 = (-1/2)x + 2
    times 2 to get rid of that nasty fraction

    6x + 54 = -x + 4
    7x = -50
    x = -50/7

    then y = x+9 = -50/7 + 9 = 13/7

    check:
    in #1:
    3y = (-1/2)x + 2
    LS = 3(13/7) = 39/7
    RS =(-1/2)(-50/7) + 14/7
    = 25/7 + 14/7 = 39/7 = LS

    my answer is correct.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question